States of Credit : Size, Power, and the Development of European Polities - Stasavage, David (Book collections on Project MUSE., 2011)
States of Credit provides the first comprehensive look at the joint development of representative assemblies and public borrowing in Europe during the medieval and early modern eras. In this pioneering book, David Stasavage argues that unique advances in political representation allowed certain European states to gain early and advantageous access to credit, but the emergence of an active form of political representation itself depended on two underlying factors: compact geography and a strong mercantile presence. Stasavage shows that active representative assemblies were more likely to be s.